The reproduction of territorial stigma. Socio-spatial dynamics of a popular neighborhood in Mexico - Monteverde-Ávalos, Miguel Ángel (2024)
This article explores the reproduction of territorial stigmatization in the San Agustín neighborhood, located in Ecatepec, Mexico. Drawing on 21 months of ethnographic research, the article analyzes how territorial stigma is produced and reproduced through the discourses, practices, and interactions of multiple actors positioned at different levels. It argues that stigma unfolds internally as social differentiation, creating a normative structure based on criteria of moral superiority and inferiority. This is manifested in the use of derogatory social categories to refer especially to younger inhabitants and in forms of symbolic distancing among neighbors. The results underscore the moral dimension of stigma and its role in the construction of symbolic and social boundaries in contexts of urban relegation. The study concludes that the reproduction of stigma in the neighborhood is due to a structure based on criteria of superiority and inferiority among residents, which is sustained by a moral evaluation that normalizes the dominant urban symbolic order of central Mexico.